2012
DOI: 10.1104/pp.112.204149
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Regulation of Soybean Nodulation by Acidic Growth Conditions

Abstract: Mechanisms inhibiting legume nodulation by low soil pH, although highly prevalent and economically significant, are poorly understood. We addressed this in soybean (Glycine max) using a combination of physiological and genetic approaches. Split-root and grafting studies using an autoregulation-of-nodulation-deficient mutant line, altered in the autoregulation-of-nodulation receptor kinase GmNARK, determined that a systemic, shoot-controlled, and GmNARK-dependent mechanism was critical for facilitating the inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 63 publications
5
58
1
1
Order By: Relevance
“…4). Lin et al (2012) reported similar result that shoot dry weight in pH 6.8 and pH 4 is not significantly different. Different result was reported by Murata et al (2003) that decreasing solution pH and Ca concentration decreased the shoot dry weight.…”
Section: Resultssupporting
confidence: 54%
“…4). Lin et al (2012) reported similar result that shoot dry weight in pH 6.8 and pH 4 is not significantly different. Different result was reported by Murata et al (2003) that decreasing solution pH and Ca concentration decreased the shoot dry weight.…”
Section: Resultssupporting
confidence: 54%
“…35 Root apices are the primary sites of Al 3+ accumulation and therefore suffer more pH also significantly reduces processes occurring downstream of, or in parallel to, root-hair infection. This includes the expression of early nodulation genes, 71 initial cell division events and primordia establishment. However, the precise mechanisms resulting in these reductions remain unclear.…”
Section: Plant Growth In Low Ph Soilmentioning
confidence: 99%
“…Recently, split-root and grafting studies using soybean grown in low pH conditions revealed a novel systemic mechanism that acts via GmNARK in the shoot to inhibit nodulation of the root (Lin et al 2012;Ferguson et al 2013). This suggests that soil acidity may act via a CLE peptide to suppress nodulation.…”
Section: Other Inducing Factorsmentioning
confidence: 99%